The Notch signaling pathway is required to specify muscle progenitor cells in Drosophila. - Giebel, B. (Mechanisms of Development, 1999)
Organization and function of the Notch signaling pathway in Drosophila are best understood with respect to its role in the process of selection of neural progenitor cells. However, there is evidence that, besides neurogenesis, the Notch signaling pathway is involved in several other developmental processes, one of which is the selection of muscle progenitor cells. Thus, the number of these cells is increased in neurogenic mutants, and it has been proposed that muscle progenitor cells are selected from clusters of equivalent cells expressing genes of the achaete-scute gene complex (AS-C). Here, I present evidence for the participation of additional elements of the Notch signaling pathway in myogenesis. Gal4 mediated expression of a Notch variant, E(spl) and Hairless shows that the selection of muscle progenitor cells obeys principles apparently identical to those acting at the selection of neural progenitor cells.